Assessing the current status of the cave scorpion Euscorpiopscavernicola Lourenço & Pham, 2013 (Scorpiones: Euscorpiidae) in northern Vietnam - Sac, Pham Dinh (Academia Journal of Biology, 2016)
Status survey of the cave scorpion, Euscorpiops cavernicola, was carried in a cave system of Bac Kan province. A total of 56 (9 adults) and 45 (7 adults) individuals were recorded during the years 2014 and 2015, respectively. This species is only known from Hua Ma cave, which is strongly threatened by tourism development. Based on the current area of occupancy (AOO) and extent of occurrence (EOO) of E.cavernicola, associated with its recent decline in both AOO and number of individuals, this species can be classified as Critically Endangeredby IUCN.